TINJAUAN KEBIJAKAN DAN STRATEGI MANAJEMEN PENDIDIKAN: IMPLEMENTASI DALAM KONTEKS MASA DEPAN - Muadifah, Muadifah; Hayadi, B. Herawan; Yusuf, Furtasan Ali; Agustina, Agustina; Suheti, Suheti; Rohim, Rouf (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2023)
The development of information and communications technology (ICT) has become a major driver in the transformation of education systems throughout the world. This abstract explores the important role of ICT in the context of education policy, exploring how its use can be increased to support the development of education that is adaptive and responsive to global change. The main focus includes aspects of learning quality, educational accessibility, and curriculum relevance. In this analysis, it was found that ICT is not only a supporting tool, but a fundamental foundation for creating a dynamic learning environment. Strong integration between progressive policies and holistic ICT use strategies is needed to achieve inclusive education goals.